BUB1 Is Identified as a Potential Therapeutic Target for Pancreatic Cancer Treatment - Li, Ming; Duan, Xiaoyang; Xiao, Yajie; Yuan, Meng; Zhao, Zhikun; Cui, Xiaoli; Wu, Dongfang; Shi, Jian (Frontiers in Public Health, 2022)
Pancreatic cancer is one of the most challenging cancer types in clinical treatment worldwide. This study aimed to understand the tumorigenesis mechanism and explore potential therapeutic targets for pancreatic cancer patients. Single-cell data and expression profiles of pancreatic cancer samples and normal tissues from multiple databases were included. Comprehensive bioinformatics analyses were applied to clarify tumor microenvironment and identify key genes involved in cancer development. Immense difference of cell types were shown between tumor and normal samples. Four cell types (B cell_1, B cell_2, cancer cell_3 and CD1C+_B dendritic cell_3) were screened to be significantly associated with prognosis. Three ligand-receptor pairs including CD74-MIF, CD74-COPA and CD74-APP greatly contributed to tumorigenesis. High expression of BUB1 (BUB1 Mitotic Checkpoint Serine/Threonine Kinase) was closely correlated with worse prognosis.CD1C+_B dendritic cell_3 played a key role in tumorigenesis and cancer progression possibly through CD74-MIF. BUB1 can serve as a prognostic biomarker and a therapeutic target for pancreatic cancer patients. The study provided a novel insight into studying the molecular mechanism of pancreatic cancer development, and proposed a potential strategy for exploiting new drugs.